The relative age effect in school sports - Gil, S. M.; Bidaurrazaga-Letona, I.; Esain, I.; Irazusta, J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: An overrepresentation of participants born in the first months after the cut-off date, known as the Relative Age Effect (RAE), has been observed in some sports, such as football, hockey, rugby and basketball, particularly in elite youth competitions (1). However, less is known about this phenomenon in lower performance levels. Thus, the aim of the present study was to investigate the presence of the RAE in different sports at school level. Methods: The date of birth of 38644 participants, aged 9-15 years old, of the school sports was analyzed (65.1% boys and 34.8% girls). These children participated in 40 different sports. Football and basketball had 3 and 2 different competition levels, respectively. The percentage of children born in each semester (1S: January-June and 2S: July-December) was compared to the distribution of the children born in the same period using a Chi square Goodness of Fit. Results: The most popular sport in boys was football (57.4%) followed by basketball (7.3%) and in girls basketball (28%), rhythmic gymnastics (10.6%), handball (9.7%), football (9.4%) and athletics (8.7%). In boys, there was an overrepresentation of participants born in the 1S in football (52.7% vs. 47.6%; p<0.001), basketball (52.4% vs. 47.6%; p<0.05), and also in the whole group (51.7% vs. 48.3%; p<0.001). This uneven distribution was the largest in the highest competition level of the youngest football players aged 9-10 years old (68.5% vs 31.5%, p<0.001). In girls, the overrepresentation was significant in athletics (52.9% vs. 47.1%; p<0.05), basketball (54.2% vs 45.8%; p<0.001), football (54% vs 46%; p<0.05), Basque pelota (59.9% vs. 40.1%; p<0.05) and the total (52% vs. 48%; p<0.001). Within basketball there was a significantly uneven distribution in the highest competition level (61% vs. 39%; p<0.001). Discussion: In school sports the RAE is particularly evident in the most popular sports and in the highest competition levels, even at the youngest ages, both in boys and girls. This implies that there is a selection process towards the participants born in the first months after the cut-off date, presumably due to their larger body size and a better physical performance (2). A special effort should be made to assure that all children have the same opportunities to participate in the sport, particularly from the very young ages. Acknowledgements We would like to thank the Provincial Council for School Sports (Bizkaiko Foru Aldundia) for the collaboration and the data provided.